1995
DOI: 10.1128/aem.61.3.1133-1137.1995
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that water transmits Vibrio vulnificus biotype 2 infections to eels

Abstract: Vibrio vulnificus biotype 2 is classically considered an obligate eel pathogen. However, it has recently been associated with one human septicemic case. In this paper, the opportunistic behavior of this pathogen is discussed. The bacterium can survive alone in brackish water or attached to eel surfaces for at least 14 days. It is able to spread through water and infect healthy eels by using skin as a portal of entry. These results suggest that water and infected eels may act as reservoirs of infection. A capsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
93
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 21 publications
10
93
0
Order By: Relevance
“…On studying the adherence and chemotaxis to different types of mucus, the differences between wild-type and mutant strains were more remarkable. The mucus was selected as substrata because VSE is able to resist the bactericidal action of mucus (Amaro et al, 1995) and colonize the mucus surface of eels by forming biofilms (Marco-Noales et al, 2001). Our results demonstrated that the wild-type strain was significantly more adherent and chemoattracted towards all types of eel mucus than the mutant strain.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…On studying the adherence and chemotaxis to different types of mucus, the differences between wild-type and mutant strains were more remarkable. The mucus was selected as substrata because VSE is able to resist the bactericidal action of mucus (Amaro et al, 1995) and colonize the mucus surface of eels by forming biofilms (Marco-Noales et al, 2001). Our results demonstrated that the wild-type strain was significantly more adherent and chemoattracted towards all types of eel mucus than the mutant strain.…”
Section: Discussionmentioning
confidence: 81%
“…c. LD50 is expressed as cfu per fish in case of i.p. injection and cfu per ml in case of bath infection (Amaro et al, 1995). d. Survival index calculated as the ratio between final and initial bacterial counts.…”
Section: Isolation and Characterization Of Dvvp Mutantmentioning
confidence: 99%
“…The evidence shows that the pathogenic strains of A. hydrophila may be transmitted from the intestine to the blood circulation and may cause systemic infection, such as MAS, in the body of fish. Information on the portals of entry for fish pathogens usually comes from observations on fish tissues using microscopic evaluations, microbiological culture, and radioactive tracer techniques or by following the exposure of the host to a green fluorescent protein-labelled pathogen (Ventura & Grizzle 1987;Amaro, Biosca, Fouz, Alcaide & Esteve 1995;Svendsen, Dalmo & Bogwald 1999;Ling, Wang, Lim & Leung 2001;O'Toole, von Hofsten, Rosqvist, Olsson & Wolf-Watz 2004;Ringø, Mikkelsen, Kaino, Olsen, Mayhew & Myklebust 2006;Chen, Yan, Wang, Zhuang & Wang 2008). However, all these previous studies are experimental challenges, and we are trying to resolve this issue from an in-field perspective.…”
Section: Discussionmentioning
confidence: 99%
“…LD50 is expressed as cfu per gr in case of i.p. injection and cfu per ml in case of bath infection (Amaro et al, 1995). b.…”
Section: Vep20 Is Involved In Resistance To the Eel Innate Immunitymentioning
confidence: 99%
“…• Colonization. The eels were bath infected with the wild type or mutant strain grown overnight in LB-1 at a dose equivalent to the LD50 of the wild-type strain (Amaro et al, 1995). A total of 24 eels per strain were infected, and six eels were immersed under the same conditions in PBS-1.…”
Section: Isolation Of Mutant and Complemented Strainsmentioning
confidence: 99%